Increasing Levels of Hypurat Acid in Urin Shoes Craftsmen Tambak Oso Wilangun, Surabaya - Taufik Ikhtiar, Erwan; Nur Hakim, Luqman; Azizah, R.; Keman, Soedjajadi (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
The home industry in the Tambak Oso Wilangun sub-district, Benowo District, Surabaya City was a center for producing shoes in Surabaya. From the entire production process there was a chemical used as a shoe adhesive, namely glue. Toluene contained in the glue used as an adhesive was very volatile so easily inhaled and enters the respiratory tract of workers. The liver and kidneys had an important role in producing toluene metabolites, namely hippuric acid, which were then excreted very quickly into the urine. Urinary hippuric acid is the main metabolite of toluene and has long been considered a biomarker of toluene exposure. The study is based on observational analytical research method while the design uses a cross-sectional study in 2 populations consisting of the exposed group and the unexposed group. The sample size for two groups is 22 people. Measurements of hypuric acid levels using HPLC-UV. The level of hypuric acid in the exposed group had mean value 9,23 mg/g of creatinine was higher than the unexposed group has mean 8,21 mg/g of creatinine. The characteristics respondent related to the levels hypuric acid was the length of work and smoking habits. Conclusion: The level of hypuric acid were higher in the exposed group than the unexposed group.